Investment Policy Review - Bosnia and Herzegovina - Conference des Nations Unies sur le commerce et le développement (United Nations, 2015)
Bosnia and Herzegovina is a transitional economy striving towards European integration. Soon after independence from the Socialist Federal Republic of Yugoslavia in 1992, Bosnia and Herzegovina plunged into a conflict which came to an end with the signing of the Dayton Peace Accords in 1995. Since then, Bosnia and Herzegovina has been committed to democracy and the transition to a market economy.